Dexmedetomidine vs propofol for gastrointestinal endoscopy: A meta-analysis. Issue 7 (November 2017) - Nishizawa, Toshihiro; Suzuki, Hidekazu; Hosoe, Naoki; Ogata, Haruhiko; Kanai, Takanori; Yahagi, Naohisa
Background and aim: Several randomized controlled trials have compared sedation with dexmedetomidine and propofol in gastrointestinal endoscopy, with contradictory results. We conducted a meta-analysis of data from randomized controlled trials that compared dexmedetomidine with propofol. Methods: We searched PubMed, the Cochrane library, and the Igaku-chuo-zasshi database for randomized trials eligible for inclusion in our meta-analysis. We identified six eligible randomized trials from the database search, and compared the effect of propofol versus dexmedetomidine with respect to: (a) patient's satisfaction level, (b) body movement or gagging, (c) cardiopulmonary complications, and (d) change in heart rate. Data from eligible studies were combined to calculate pooled risk difference (RD) or weighted mean difference (WMD). Results: Compared to propofol, dexmedetomidine significantly decreased the patient's satisfaction level (WMD: –0.678, 95% confidence interval (CI): –1.149 to –0.207, p  = 0.0048), and there was no significant heterogeneity among the trial results. The pooled RD for developing body movement or gagging when using dexmedetomidine was 0.107 (95% CI: –0.09 to 0.305, p  = 0.288), with no significant differences. Compared with propofol, the pooled RD for hypotension, hypoxia, and bradycardia with dexmedetomidine sedation were –0.029 (95% CI: –0.11 to 0.05), –0.080 (95% CI: –0.178 to 0.018), and 0.022 (95% CI: –0.027 to 0.07), respectively, with no significant differences. Compared to propofol, dexmedetomidine significantly decreased the heart rate (WMD: –10.41, 95% CI: –13.77 to –7.051, p  ≤ 0.0001), without significant heterogeneity. Conclusions: In gastrointestinal endoscopy, patient satisfaction level was higher in propofol administration, when compared to dexmedetomidine. The risk of complications was similar.